Educational Robotics in a Non-Formal Context: A Comparative Analysis of Attitudes in an NGO (2023–2024) - Ribeiro, Carlos Eduardo; Palácios, Rodrigo H. Cunha; Todt, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This study investigates the impact of educational robotics interventions on the attitudes of young people in a Non-Governmental Organization (NGO) over two years (2023–2024). Using the Robotics Attitudes Measurement Instrument, four constructs were assessed: willingness to learn, self-confidence, computational thinking, and teamwork. A significant positive progression was observed in the mean scores of all constructs between 2023 and 2024, notably in Willingness to Learn (from 3.06 to 3.61) and Self-Confidence (from 2.76 to 3.24). Analyses, including gender differences, correlations between constructs, and qualitative reports from teachers, demonstrate the potential of robotics to foster engagement and positive attitudes in non-formal educational settings.